A (supra)nationalist personality? The Big Five's effects on political-territorial identification. (June 2021) - Curtis, K Amber; Miller, Steven V
Recent work suggests personality affects the subjective psychological weight one attaches to an identity. This study extends prior findings showing a static effect on European identification in a single country by investigating whether a similar systematic relationship exists for a wider range of political-territorial identities (regional, national, supranational, and exclusively nationalist) across different country contexts (Germany, Poland, and the United Kingdom) and over time (2012–2018). Original cross-national and panel survey data show that different traits predict both the type and degree of inclusivity of individuals' identity attachments. These results contribute to the growing scholarship surrounding personality's effects on EU support while underscoring the impact predispositions have on citizens' sociopolitical orientations. They especially illuminate the contrasting profiles associated with those who identify as exclusively nationalist versus supranational European.